LES PROBLEMES LIES A LA DIFFUSION DE L’INFORMATION/PROBLEMS CONNECTED WITH MAKING INFORMATION AVAILABLE - Martin, Francois (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF